Stress em profissionais de enfermagem: um estudo etnográfico - Martins, Maria das Graças Teles [UNIFESP] (2010)
The aim of this study was to apprehend, by means of an ethnographic approach, the social representations of stress in nurses that work at the Intensive Therapy Unit and Surgical Unit in a public hospital of João Pessoa (PB). We intended to understand how nurses think, feel, elaborate, associate and represent stress in different contexts of their professional and social lives. Through narratives and verbal and non-verbal discourses of the interlocutors, we tried to verify how they elaborate what they call stress, associating and defining it in their social and cultural quotidian.